Does growing vegetables in plastic greenhouses enhance regional ecosystem services beyond the food supply? - Chang, Jie; Wu, Xu; Wang, Yan; Meyerson, Laura A; Gu, Baojing; Min, Yong; Xue, Hui; Peng, Changhui; Ge, Ying (Frontiers in Ecology and the Environment, 2013)
In recent years, plastic greenhouse vegetable cultivation (PGVC) has expanded worldwide, particularly in China, where it accounts for more than 90% of all global PGVC operations. As compared with conventional agricultural methods, PGVC has doubled crop yields by extending growing seasons and intensifying agriculture. PGVC also offers more ecosystem services relative to conventional approaches, including greater soil carbon sequestration, lower water consumption, and improved soil protection at regional scales. The economic benefits of this easily implemented agricultural method are attractive to small‐holder farmers. However, greater environmental impacts (eg greenhouse‐gas emissions, generation of large amounts of plastic waste) are associated with PGVC than with conventional approaches. Here, we review what is currently known about PGVC and identify future research priorities that will comprehensively assess the ecosystem services offered by this method of cultivation, as well as its environmental impacts and socioeconomic benefits.

Quantification of net carbon flux from plastic greenhouse vegetable cultivation: A full carbon cycle analysis - Wang, Yan; Xu, Hao; Wu, Xu; Zhu, Yimei; Gu, Baojing; Niu, Xiaoyin; Liu, Anqin; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Pollution, 2011)

Agricultural carbon flux changes driven by intensive plastic greenhouse cultivation in five climatic regions of China - Wu, Xu; Ge, Ying; Wang, Yan; Liu, Dong; Gu, Baojing; Ren, Yuan; Yang, Guofu; Peng, Changhui; Cheng, Jihua; Chang, Jie (Journal of Cleaner Production, 2015)

Assessment of net ecosystem services of plastic greenhouse vegetable cultivation in China - Chang, Jie; Wu, Xu; Liu, Anqin; Wang, Yan; Xu, Bin; Yang, Wu; Meyerson, Laura A.; Gu, Baojing; Peng, Changhui; Ge, Ying (Ecological Economics, 2011)